Elderly Severe Hyponatremia: Case Report and Literature Review - Gabriela de Andrade Lopes; Laiane Cristina de Camargos Silva; Livia Lemos Oliveira; Thais Carvalho Marinelli; Rogério Saint-Clair Pimentel Mafra; Ivana Mussel (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Most  authors  define  hyponatremia  as  a  serum  sodium concentration  below  the  lower  limit  of  normality,  lower  than 135  meq/L1,  but  there  is  still  a  discussion  on  best  values  of reference [1]. Characterized as a hydroelectrolytic disorder, hyponatremia is  very  common  in  elderly,  hospitalized  individuals  and  may be commonly associated with neoplasms, liver cirrhosis, heart failure  and  renal  failure.  Physiologically,  it  is  inferred  that the  increase  of  water  triggers  hyponatremia  and  not  a  direct sodium  low,  even  in  situations  of  hypovolemic  hyponatremia [1]. Thus,  excess  water  leads  to  an  increase  in  serum  sodium dilution, and as a negative feedback under normal conditions,the level of antidiuretic hormone (ADH) decreases, so that the kidney collecting tubules become impermeable to water and It can be excreted in urine. However, in pathological situations, there  may  be  a  decompensation  in  this  functioning,  with several etiologies related to inadequate ADH secretion, such as antidepressant medications use [2].